Analysis of Extreme Weather Causes of Flooding in Manado North Sulawesi - Ni Luh Made Anik Evaria; Rafa Zafirah Istiqomah (PT. Padang Tekno Corp, 2024)
On January 27 and 28 2023, Manado City was hit by heavy rain which caused several areas to experience significant flooding. The high intensity of rain during that period reached extreme levels, resulting in the inundation of several areas and submerging hundreds of residents' houses in 22 villages or sub-districts and 7 sub-districts in Manado. In studying this event, this research investigates the factors that influence extreme weather in Manado, observing sea surface temperature data, streamlines, air observations, the Southern Oscillation Index (SOI), and the Indian Ocean Dipole (IOD). The analysis shows that the positive SOI and negative IOD phenomena significantly impact extreme weather in the region. Cumulonimbus (Cb) clouds drove the atmospheric conditions formed on January 27 and 28 2023 and air flows from the Indian Ocean which brought wet air masses into Indonesian territory. High sea surface temperatures, reaching 28-29°C, also play a role in the intensive growth of rain clouds. Based on atmospheric conditions seen from radiosonde observation data, the stability index value shows that unstable conditions trigger heavy rain which causes flooding